PERAN HUMOR GURU DALAM MENGELOLA STRESS AKADEMIK SISWA - Syeh Sarip Hadaiyatullah; Sri Legi Rahmadani; Cindy Afsa Harahap; Alya Putri Mora (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
Academic stress is a common problem experienced by students as a result of learning demands, task pressure, and expectations from the school environment. If not properly managed, this condition can decrease learning motivation, cause fatigue, and hinder students’ psychological and academic development. This study aims to examine the role of teacher humor in managing students’ academic stress through a comprehensive literature review. Humor is understood as a pedagogical strategy that can create a positive classroom atmosphere, reduce emotional tension, and enhance interpersonal relationships between teachers and students. This research employs the library research method, which involves collecting, reviewing, and analyzing various literature sources such as scientific journals, books, research reports, and academic articles relevant to the theme of teacher humor and academic stress. The findings indicate that teacher humor plays a significant role in helping students reduce academic stress. Appropriate humor can create an enjoyable learning environment, increase students’ self-confidence, strengthen the positive psychological climate of the classroom, and help students feel more relaxed in facing academic demands. In addition, humor improves the quality of teacher–student interaction, making students more open in expressing the academic difficulties they encounter.